miR-134-3p Regulates Cell Proliferation and Apoptosis by Targeting INHBA via Inhibiting the TGF-β/PI3K/AKT Pathway in Sheep Granulosa Cells - Xinai Huang; Yongjin Bao; Fan Yang; Xiaodan Li; Feng Wang; Chunxiang Zhang (Biology)
Inhibin β-A (INHBA), a TGF-β superfamily member, is crucial for developing follicles. Although miRNAs are essential for post-transcriptional gene regulation, it is not yet known how they affect the expression of INHBA during follicle development. Using bioinformatics analyses, miR-134-3p was found, in this investigation, to be a crucial microRNA that targets INHBA in sheep GCs. Furthermore, when the follicular diameter expanded, there was a discernible decline in miR-134-3p expression. The miR-134-3p overexpression markedly reduced the proliferation of GCs, whereas its knockdown augmented it. Moreover, cell cycle progression was enhanced by miR-134-3p overexpression. Furthermore, miR-134-3p overexpression heightened GC apoptosis, while its knockdown reduced it. Importantly, miR-134-3p overexpression blocked the PI3K/AKT/mTOR axis, whereas its knockdown stimulated it. Overall, the outcomes of transfections with INHBA and miR-134-3p showed that, in sheep GCs, miR-134-3p targets INHBA to control cell proliferation and apoptosis. In summary, these results add to our understanding of the molecular mechanisms involving important miRNAs in ewe fecundity by indicating that miR-134-3p influences cell proliferation, cell apoptosis, and the TGF-β/PI3K/AKT/mTOR axis, which, in turn, influences the follicular development of sheep GCs.